Dental caries status among elementary students at Medowo III Elementary School, Kandangan, Kediri, East Java - Pramusita, Adya; Triwardhani, Ari; Putranti, Nurul Aisyah Rizky; Rahmawati, Dwi; Nugraha, Alexander Patera; Devitha, Maria; Megantara, Riizko Wira Artha; Noor, Tengku Natasha Eleena binti Tengku Ahmad (Faculty of Dental Medicine Universitas Airlangga, 2024)
Background: Dental caries is frequently observed in children. Increasing the awareness of oral health among school-age children is anticipated to decrease the occurrence of dental caries. Purpose: The aim of this study was to determine the prevalence of dental caries among students in Medowo III elementary school using dmft/DMFT index. Methods: A cross-sectional descriptive study was carried out among the entire student at Medowo III elementary school. The dental caries of each student were assessed using the dmft and DMFT indices. The assessment of variable distribution was conducted using the Shapiro-Wilk test. The dmft/DMFT values were compared between different age groups and genders using either the Student's t-test or the Mann-Whitney test. The data was processed using a significance level of p < 0.05. Results: The study included a total of 43 students. The average caries index in primary dentitions was markedly greater than in permanent dentitions. According to WHO, the prevalence of dental caries was very high in the primary dentition of students aged 7-9 years. No notable disparities were detected between female and male students in relation to the caries index of both primary and permanent teeth. However, the average caries index of primary teeth was considerably higher in middle-childhood students compared to preadolescence students. Conclusion: The dental caries prevalence among students in Medowo III elementary school were still high. Therefore, oral health prevention program was needed in order to enhance the community's awareness toward dental caries.